(untitled) (Economic and Political Thought, 2019)
The aim of the publication was to analyse political and research and development conditions for the level of defense spending in the USA. They are of key importance for shaping the Pentagon military budget in conditions in which it seems very difficult to grasp the state of threats to which an ‘adequate’ level of financing would be an answer. The debate on the level of defense expenditures required to ensure the security of the state is everlasting. There are two decisive elements for determining defense expenditures. First, political circumstances, both of internal ones (the Republicans are more inclined to spend more on defense than the Democrats) and external ones (using military capabilities to keep hegemonistic position of the United States, including vis-à-vis allies and adversaries); second, research and development circumstances aimed at ensuring technological supremacy of the United States in the world and having positive implications for military and civilian sectors.